International consensus statement on the assessment of interprofessional learning outcomes. (3rd April 2017) - Rogers, Gary D.; Thistlethwaite, Jill E.; Anderson, Elizabeth S.; Abrandt Dahlgren, Madeleine; Grymonpre, Ruby E.; Moran, Monica; Samarasekera, Dujeepa D.
Abstract: Regulatory frameworks around the world mandate that health and social care professional education programs graduate practitioners who have the competence and capability to practice effectively in interprofessional collaborative teams. Academic institutions are responding by offering interprofessional education (IPE); however, there is as yet no consensus regarding optimal strategies for the assessment of interprofessional learning (IPL). The Program Committee for the 17th Ottawa Conference in Perth, Australia in March, 2016, invited IPE champions to debate and discuss the current status of the assessment of IPL. A draft statement from this workshop was further discussed at the global All Together Better Health VIII conference in Oxford, UK in September, 2016. The outcomes of these deliberations and a final round of electronic consultation informed the work of a core group of international IPE leaders to develop this document. The consensus statement we present here is the result of the synthesized views of experts and global colleagues. It outlines the challenges and difficulties but endorses a set of desired learning outcome categories and methods of assessment that can be adapted to individual contexts and resources. The points of consensus focus on pre-qualification (pre-licensure) health professional students but may be transferable into post-qualification arenas.